Is open lateral anal sphincterotomy really a safe and satisfactory treatment option for refractory chronic anal fissures? - a prospective study - Mir, Shabir Ahmad; Lone, Zubair Gull; Dar, Waseem Ahmad; Wani, Mumtazdin (International Journal of Research in Medical Sciences, 2019)
Background: Chronic anal fissure is a familiar entity in surgical outdoor departments of hospitals in our valley. The muslim women are usually reluctant to expose their anal canal related pathologies to male surgeons, letting anal fissures to reach the chronic stage. Under this background, the present study was conducted to look for the feasibility of lateral anal sphincterotomy in the management of chronic anal fissure in our patients. Methods: This prospective study was carried out over a period of 3 years in the unit 2nd of department of surgery at SMHS (Shri Maharaja Harisingh) hospital, an associated hospital of Government Medical College Srinagar. During this period, 59 patients presented to the outpatient department with typical chronic anal fissures and were included in this study. Results: Fifty-nine patients, diagnosed on clinical evaluation as chronic anal fissure were included in this study. The age varied from 19 to 58 years with mean age of 36.38±7.14 (SD= 7.14) years. There was a female predominance, with a female to male ratio of 2.1:1. Fifty-two (88.1%) patients had posterior midline fissure and 7 (11.8%) patients had an anterior anal fissure. Thirty-one patients were not satisfied with the conservative treatment and insisted for surgical management. All 31 patients were managed by open lateral anal sphincterotomy. Conclusions: Lateral anal sphincterotomy (LAS) is a safe and effective method of management for chronic refractory anal fissures. The complications are minimal and negligible.